Autopsi Forensik Sebagai Upaya Mencapai Kepastian Hukum Pada Kasus Kematian Tidak Wajar - Afiful Jauhani, Muhammad; Wahyu Pratiwi, Yoga; Supianto, Supianto (Prodi Ilmu Hukum Fakultas Hukum Universitas Islam Jember, 2023)
Autopsy is a medical examination of a corpse to determine the cause of death. Forensic autopsies for judicial purposes have been regulated in Article 133 and Article 134 of the Code of Criminal Procedure, even Article 222 of the Criminal Code has also regulated criminal sanctions against parties who intentionally hinder forensic autopsies, but it is undeniable that there are still obstacles in its implementation. This study aims to analyze the essential role of forensic autopsies for legal certainty through analysis of several court decisions and literature review using normative juridical methods with statutory and conceptual approaches. Forensic autopsies has scientific validity. Application of the principle of causality is very important in law enforcement for a fair and correct decision so that it can fulfill a sense of justice for victims, perpetrators and also the community. The accurate cause of death through a forensic autopsy, is a material justification that can be verified scientifically for discovering the truth.